Will registries slow down or accelerate innovation? - Carr, A (British Editorial Society of Bone and Joint Surgery, 2019)
The increasing use of regional and national registries of surgical implants has raised concerns that the cost and consequences of these initiatives will adversely influence innovation. The opposite appears to be true, with no evidence of a reduction in overall innovation and an association of increased innovation in countries with more evaluation using registries.